Transferência de tecnologia em organizações hospitalares: suporte multicritério à decisão com base na teoria da capacidade absortiva - Schimith, Cristiano Descovi (Universidade do Vale do Rio dos Sinos, 2017)
This thesis deals with the theme technology transfer inside hospital organizations. In hospitals, the decision to transfer a technology passes through a management body that can assume both roles of demanding and deciding over the technology, which can result in zero-sum competitions or agency dilemmas. This research explores how the process of technology transfer occurs in these organizations, resulting in a metamodel and a method to support this type of decision. The meta-model is proposed under the lens of absorptive capacity theory. The thesis defended by this research is that, identifying process and factors, and analyzing the criteria adopted from the absorptive capacity theory perspective, it is possible to point out biases and to improve the assertiveness of decisions that occur throughout the process of hospital technology transfer. The artifacts produced are lined on the search for generality, although they are based on a qualitative research. Sources of information include documentary analysis, literature review, interviews with members of hospital organizations, and interviews with technology transfer specialists. The theoretical contribution includes a perspective analysis of the technology transfer process inside hospital organizations, using the absorptive capacity theory perspective, and resulting in a multicriteria meta-model to support decision-making. In addition, the main empirical contribution is due to a different way to analyze the hospital technology transfer process, especially considering the dimensions proposed by the absorptive capacity theory, and using a multicriteria approach to rationalize the decisions during the process of technology transfer.
Keywords: Transferência de tecnologia; Organizações hospitalares; Teoria da capacidade absortiva; Suporte multicritério à decisão; Technology transfer; Hospital organizations; Absorption capacity theory; Multicriteria decision support; ACCNPQ::Engenharias::Engenharia de Produção